Analysis of Informal Child Education to The Beggar Family Hadipolo Village Chinatown Complex Kudus Regency - Rini, Setiana Eka; Arsal, Thriwaty; Suhandini, Purwadi (Universitas Negeri Semarang, 2018)
The role of parents influences the informal education of children. Informal education is education obtained from families and the surrounding environment. This study aims to determine the parenting style in informal child education in beggar families in Hadipolo Village, Jekulo District, Kudus Regency and to know the social interaction of beggar children in the community. The research method is qualitative. The informants in this study were beggars 'families, beggars' children and surrounding communities who met the data needs in the study. Data validity techniques using data triangulation techniques. Data analysis is carried out through four stages: data collection, data reduction, data presentation, and conclusion. The results of the study show that informal education in beggar families runs even though informal education is more obtained from the community than the family environment itself. Informal education does not run completely in the family because of one of the factors, namely the lack of parental education and lack of parental time with children. Lastly the social interaction between beggar children and the community of the Hadipolo Chinatown complex is said to be running because of the similarity of the fate of the residents of the Chinatown complex. Unlike the case when interacting with the Hadipolo community which is already outside the community relations complex, the Chinatown complex cannot be said to be good, because of the historical factors that resulted in the interaction being reduced.